A machine learning approach to predicting and mitigating traffic congestion - Faisal, Abu Fatah Mohammed; Zahid, Chowdhury Zaber Bin; Hasan, Walid Ibne; Talukder, Shuvo (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2024.